Nitrogen fertilization, crop age at harvesting and quality of sugarcane in a moderately saline soil - Pinna Cabrejos, Jorge; Valdivia Salazar, Sergio André; Valdivia Vega, Sergio Adrián (Agrociencia Uruguay, 2019)
At Zapote C-D field, belonging to Agro Industrial Tumán enterprise, localized in Peruvian northern coast, Lambayeque Department the present study was carried out. In this field with moderately saline soil (1.98-8.66 dSm-1), five N rates (180, 250, 320, 390,460 kg N ha-1) per age, with four replications and one control plot without N per age were studied, at five harvesting ages (12.3, 15.5, 20.0, 23.3,26.5 months). Sugarcane cultivar H32-8560 (plant cane) was developed. Sugarcane quality analysis: Sucrose, brix, purity, reducing sugars, fiber and humidity; were made at each harvesting. Variance Analysis for studying N doses and cane age effects on sugarcane quality were made. Regressions were made between quality results, with mean salinity of first soil 60 cm of each plot, at planting, with N rates, and with cane age. It was found that N applications don’t affect sugarcane quality. Moderately soil salinity at planting is not related with none of sugarcane quality characteristics. Sugarcane quality is not affected by N rates or soil salinity. Sugarcane quality varies with harvesting ages, having similar behavior to the one of non-saline soils. Lack of water does not affect ripening of sugarcane.